Mao. 5 Exorcise your destiny - Takahashi, Rumiko, 1957- (Shonen Sunday comics special., 2022)
"When Nanoka is transported back in time to a supernatural early 20th century, she gets recruited by aloof exorcist Mao. What thread of fate connects them? Together, they seek answers...and kick some demon butt along the way! While Shiranui and his minions pursue Mao in the Taisho era, the cat demon Byoki stalks Nanoka in the present day. Meanwhile, a mysterious woman is spreading strange rumors around old Kyoto. Who is she really? Then, a stranger armed with powerful spells and mechanical weapons appears and sets his sights on a particular target..."--